Comparison of three classifications for lymph node evaluation in patients undergoing total mesorectal excision for rectal cancer - Fritzmann, Johannes; Contin, Pietro; Reißfelder, Christoph; Büchler, Markus W.; Rahbari, Nuh Nabi; Ulrich, Alexis (Langenbeck's archives of surgery, 2018)
PurposeThe present study compared the prognostic value of the lymph node ratio (LNR) and the 6th and the 7th TNM edition as three different lymph node classifications for rectal cancer patients.MethodsA total of 630 patients who underwent total mesorectal excision for primary rectal cancer between October 2001 and December 2007 were included. Prognostic factors of overall survival were analyzed using Cox proportional hazards models.ResultsThe median follow-up was 36.1 months and the 5-year overall survival rate was 70.3 ± 4.7%. The median number of lymph nodes was 15.0 (12.0-19.0). All three lymph node evaluations correlated with survival (p < 0.0001). The assessment of nodal status in the 7th TNM edition enabled further prognostic stratification. The prognostic value of the three classifications were independent of neoadjuvant therapy and lymph node count. On multivariate analyses, the N2 stage of the 6th TNM edition (Hazard ratio 2.08; 95% confidence interval 1.21-3.58) and the N2b stage of the 7th TNM edition (2.18; 1.17-4.07) correlated with poor survival. A LNR of 0.42-0.69 was also associated with unfavorable prognosis (2.97; 1.46-6.03), as was an LNR > 0.69 (2.51; 1.04-6.05). The LNR did not provide prognostic information in addition to the N stage of the TNM classifications.ConclusionsThe evaluated lymph node classifications were of comparable prognostic utility in patients with rectal cancer. The LNR did not provide prognostic information in addition to the N stage of the TNM classifications.